(untitled) (European Journal of Marketing and Economics, 2025)
The article tackles the issue of cultural diversity as a phenomenon present in many multicultural communities that encompass representatives of different ethnic, national or religious traditions. Bosnia-Herzegovina provides an example of one of such communities, subject to analysis within the framework of this paper. The author firstly concentrates on the issues related to terminology of “cultural diversity” and “non-governmental organization”, their specificity and interpretations. Then, an Introduction to Bosnian multiculturalism is made, displaying its local features, followed by a presentation of various NGO’s activities with reference to Bosnian war and its aftermath. The focus is on the regional organizations that make the effort to reconstruct the multicultural bond, revealing its educational potential. The final analysis considers intercultural aspects of such approach to cultural differences that can become a point of reference in educational projects oriented at cross-cultural learning and intercultural dialogue. The latter, in turn, could contribute to the process of shaping constructive attitudes to representatives of the culturally diverse traditions.